Obesity and dissociable forms of impulsivity in young adults. (25th February 2015) - Chamberlain, Samuel R.; Derbyshire, Katherine L.; Leppink, Eric; Grant, Jon E.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Obesity is one of the leading causes of preventable morbidity and mortality, and young people are increasingly affected. The aim of this study was to examine relationships between obesity and dissociable forms of impulsivity in young adults. Methods A group of young adults (511) was recruited from city areas in the United States using media advertisements. These young adults were administered careful and extensive clinical and neurocognitive assessment in order to quantify different aspects of impulsivity (behavioral/phenomenological-, cognitive-, and personality-related measures). Associations between obesity and impulsivity were explored using multivariate analysis of variance and discriminant function analysis. Results 10.8% of the sample was obese, and 21.5% was overweight. Compared to controls, subjects with obesity showed significantly elevated rates of maladaptive gambling behaviors, monetary amounts lost to gambling, nicotine consumption, impulsive action (prolonged stop-signal reaction times in the Stop-Signal Test), and impulsive decision-making (reduced modulation of behavior as a function of risk in the Cambridge Gamble Test). Even accounting for potential confounding variables, obesity was significantly predicted by female gender, older age, more maladaptive gambling behaviors, and worse inhibitory control (stop-signal reaction times). Conclusion Obesity is associated with several dissociable forms of impulsivity in young people, especially gambling and impulse dyscontrol. Family doctors should screen for gambling problems in obese young adults. Successful treatment of nicotine dependence in young obese people is likely to require intensive weight management support. Neuropsychological deficits relating to impulsivity occur in obese people in early adulthood, and may represent vulnerability markers rather than being due to chronic untoward metabolic effects on brain function.